Clinical and Epidemiological Characteristics of Chikungunya and Dengue Infections in Provincial Hospitals of Davao de Oro, Philippines - Nestor Arce; Kobporn Boonnak; Lee Thunder Bernasor; Christian Joy Salas; Anastasia Putri; Pyae Linn Aung; Hisham Ahmed Imad; Wirongrong Chierakul; Viravarn Luvira; Benjaluck Phonrat; Weerapong Phumratanaprapin; Prakaykaew Charunwatthana (Reports)
Background: Mosquito-borne diseases such as dengue and chikungunya are endemic to tropical regions and are common causes of acute febrile illness in both adults and children. The Philippines, home to more than one hundred million residents and visited by several million tourists each year, is one such region where the risk of these diseases is endemic. Objective and Methods: To better understand the detailed situation, we estimated the proportion of these diseases in the community by conducting a prospective observational study in four provincial hospitals of Davao de Oro, Philippines, from February 2019 to February 2020. Sera from 382 study participants were used for laboratory confirmation of dengue or chikungunya by serology. Results: Dengue was diagnosed in 57.1%, chikungunya in 7.07%, and coinfection with both dengue and chikungunya in 7.3%, while the etiology was undetermined in 35.9% of the study participants. Common clinical symptoms included fever, headache, and a rash, which were overlapping symptoms that were clinically indistinguishable at the presentation to the hospital, necessitating laboratory diagnostics. Conclusions: The identification of the presence of chikungunya in Davao de Oro calls for increased awareness, improved diagnostics, and integrated disease control measures to manage outbreaks that can occur in dengue-endemic regions.